EFFECT OF LEADERSHIP AND JOB SATISFACTION ON PERFORMANCE WITH COMMITMENT MEDIATION (IN PT ALAM KAYU SAKTI SEMARANG) - Soegihartono, Soegihartono (Solusi, 2019)
ABSTRACT The purpose of the research is to test and analyze whether there is an influence of leadership and job satisfaction on the performance of employees of PT. Alam Kayu Sakti (PT. ALKA) Semarang by mediating organizational commitment. As the object of this research are permanent employees of PT. Alam Kayu Sakti (PT. ALKA) Semarang with a sample of 109 employees as respondents. The question used has been tested for validity by factor analysis and reliability with Cronbach alpha and the instruments are valid and reliable or worthy of being used as a research tool. The results of the analysis can be summarized as follows: This study can prove leadership has a positive effect on organizational commitment. This is in accordance with his theory Bass (1990). This study can prove job satisfaction has a positive effect on organizational commitment. This is according to Johlke’s (2000) study. This research can prove leadership has a positive effect on performance. This is in accordance with his theory Bass (1990). This study can prove job satisfaction has a positive effect on performance. This is in accordance with his theory Robins (1996). This study proves organizational commitment has a positive effect on performance. This is in accordance with the study of Johlke et al (2000). This study does not prove that organizational commitment mediates on the influence of leadership on performance. This is in accordance with Tri Murdoko’s research (2007). This study does not prove that organizational commitment mediates on the effect of job satisfaction on performance. This is in accordance with Yustiani’s research, Utai Dian (2005) Keywords: leadership, job satisfaction, organizational commitment and performance